The Arabidopsis transcription factor LBD15 mediates ABA signaling and tolerance of water‐deficit stress by regulating ABI4 expression. (17th September 2020) - Guo, Zhaolai; Xu, Huini; Lei, Qidong; Du, Jiancan; Li, Cheng; Wang, Chongde; Yang, Yunqiang; Yang, Yongping; Sun, Xudong
SUMMARY: To survive, sessile plants must adapt to grow and develop when facing water‐deficit stress. However, the molecular mechanisms underlying fine‐tuning of the antagonistic action between stress response and growth remain to be determined. Here, plants overexpressing Lateral Organ Boundaries Domain 15 ( LBD15 ) showed abscisic acid (ABA) hypersensitivity and tolerance of water‐deficit stress, whereas the loss‐of‐function mutant lbd15 presented decreased sensitivity to ABA and increased sensitivity to water‐deficit stress. Further analysis revealed that LBD15 directly binds to the promoter of the ABA signaling pathway gene ABSCISIC ACID INSENSITIVE4 ( ABI4 ) to activate its expression, thereby forming an LBD15–ABI4 cascade to optimally regulate ABA signaling‐mediated plant growth and tolerance of water‐deficit stress. In addition, drought stress‐induced ABA signaling promoted LBD15 expression, which directly activates expression of ABI4 to close stomata. As a result, water loss is reduced, and then water‐deficit stress tolerance is increased. The results of this study reveal a molecular mechanism by which LBD15 coordinates and balances plant growth and resistance to water‐deficit stress. Significance statement: Terrestrial plants have to adapt their growth and development for survival when facing water‐deficit stress. However, how plants fine‐tune the antagonistic action of stress response and growth remains largely unclear. This study demonstrated that LBD15 is a core regulator that fine‐tunes plant growth and the water‐deficit stress response. Under normal growth conditions (low ABA concentrations), LBD15 regulates the expression of WUSCHEL, which is involved in development of the shoot apical meristem, and that of VND7 which induces xylem vessel formation and provides mechanical strength to support the entire plant. Meanwhile, ABA signaling modulates trehalose metabolism and lipid breakdown and provides energy support for growth. Under water‐deficit stress (high ABA concentration), LBD15 is involved in ABI4‐mediated ABA signaling by promoting stomatal closure and providing protection against water loss. Meanwhile, LBD15 regulates the expression of VND7 to induce xylem vessel formation and facilitate water transport.